Oh no, now i have diabetes - Abdul Rashid, Aneesa; Devaraj, Navin Kumar (Pakistan Medical Association, 2018)
Screening plays the biggest role in the diagnosis of diabetes in primary care, however it sometimes presents with uncommon clinical features, which will need good clinical acumen to reach the elusive diagnosis. This interesting report will look at four cases in brief on how the authors managed to reach this diagnosis in unique ways.